Динамiка вивiльнення нестероїдного протизапального препарату пiроксикаму з полiмерної композицiї на основi олiгоефiруретандiiзоцiанату in vivo - Кулєш, Д.В.; Нечаєва, Л.Ю.; Галатенко, Н.А. (Видавничий дім "Академперіодика" НАН України, 2008)
Dynamics of liberation of piroxicam in vivo from polyurethane is investigated by determination of a residual quantity of piroxicam in polymeric samples after their implantation in the organisms of laboratory animals for different terms. It is shown that immobilized piroxicam liberates in the environmental fabrics of experimental animals within 90 day. More than 50% of introduced piroxicam is liberated till 14th day, which is important for the further development of the inflammatory process at a place of implantation.